BENTUK TEMPAT PERSALINAN IDEAL MENURUT IBU HAMIL - T.P, A. Y. Yan Wellyan (Jurnal Widya Manajemen & Akuntansi, 2006)
This study is to reveal attributes of an ideal clinic expected by pregnant mothers. The major data of the study are responses to the interviews with pregnant mothers and description of the attributes of the clinic as found through observation. The research is a qualitative casestudy of which it wants to uncover the attributes of an ideal clinic expected by pregnant mothers. The respondents of this study are 83 taken through a random procedure, with grouping-focused method. They represent the population because there is no more new attributes foun strarting with 67th respondent to the last respondent, 83. The researcher stopped taking the data to the 83rd respondent for he believes that there is no other new attribute. The analisis shows that the attributes expected by pregnant mothers are professional and diligent medical and non-medical workers; a comfortable, clean, tidy, and safe place; reasonably priced cos. As a resul , if the clinic is to be the first ideal place for delivering a baby, the clinic should create an image that takes care of service quality with the expected attributes, both attributes related to product, attributed related to service and attribute related to purchase.